Evaluation of quality and nursing skills in emergency department - leila yekehfallah (Journal of Holistic Nursing and Midwifery)
Introduction:‎‏ ‏Nurses are the largest and most important group in health system and play clear ‎role. Nowadays, emphasis on health‏ ‏promotion and considering client as a whole clears ‎attention to quality of nursing care.‎‏ ‏On the other hand increased knowledge of clients ‎regarding health care made the demand for satisfactory nursing services. Therefore, it is ‎necessary for nurses to achieve and improve their nursing skills. Meanwhile, emergency ward ‎nurses must be professional with a wide information and skills, adequate speed in performing ‎techniques, decision making power and also triaging clients.‎